Concentration of viruses and electron microscopy - I. D. Petrova; B. N. Zaitsev; O. S. Taranov (Вавиловский журнал генетики и селекции)
Nearly all lethal viral outbreaks in the past two decades were caused by newly emerging viruses. Viruses are often studied by electron microscopy (EM), which provides new high-resolution data on the structure of viral particles relevant to both fundamental virology and practical pharmaceutical nanobiotechnology. Electron microscopy is also applied to ecological studies to detect viruses in the environment, to analysis of technological processes in the production of vaccines and other biotechnological components, and to diagnostics. Despite the advances in more sensitive methods, electron microscopy is still in active use for diagnostics. The main advantage of EM is the lack of specificity to any group of viruses, which allows working with unknown materials. However, the main limitation of the method is the relatively high detection limit (107 particles/mL), requiring viral material to be concentrated. There is no most effective universal method to concentrate viruses. Various combinations of methods and approaches are used depending on the virus and the goal. A modern virus concentration protocol involves precipitation, centrifugation, filtration, and chromatography. Here we describe the main concentrating techniques exemplified for different viruses. Effective elution techniques are required to disrupt the bonds between filter media and viruses in order to increase recovery. The paper reviews studies on unique traps, magnetic beads, and composite polyaniline and carbon nanotubes, including those of changeable size to concentrate viral particles. It also describes centrifugal concentrators to concentrate viruses on a polyethersulfone membrane. Our review suggests that the method to concentrate viruses and other nanoparticles should be chosen with regard to objectives of the study and the equipment status of the laboratory.